2017
DOI: 10.21037/jtd.2017.07.77
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymph node dissection in surgical treatment for early stage non-small-cell lung cancer: lobe-specific or systematic?

Abstract: The standard surgical treatment for early stage non-smallcell lung cancer (NSCLC) is lobectomy or pneumonectomy with systematic lymph node dissection (SND) (1,2). In 2006, the European Society of Thoracic Surgeons (ESTS) released guidelines for intraoperative lymph node staging in NSCLC, in which intraoperative procedures for lymph nodes were classified into five groups; selected lymph node biopsy, (systematic) sampling, lobe-specific lymph node dissection (L-SND), SND, and extended lymph node dissection; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Further prospective studies, including covariates related to the time of recurrence, are required to confirm our results. Third, we excluded patients who underwent sublobar resection because lobectomy with lymph node dissection is considered the standard treatment for early stage disease ( 35 ). Finally, patients with second primary lung cancer were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Further prospective studies, including covariates related to the time of recurrence, are required to confirm our results. Third, we excluded patients who underwent sublobar resection because lobectomy with lymph node dissection is considered the standard treatment for early stage disease ( 35 ). Finally, patients with second primary lung cancer were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Especially for early-stage non-small cell lung cancer, several studies have concluded that SLND is not necessary. Many recent studies have suggested that LSLND and LNS can achieve the same therapeutic effect as SLND for early-stage NSCLC 5 , 6 , 9 , 12 , 16 , 17 . At the same time, some studies suggest that LSND and LNS can reduce the incidence of complications caused by lymph node dissection, such as lymphatic fistula, bleeding, and nerve damage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, for early-stage NSCLC, the method of lymph node Ivyspring International Publisher dissection has been controversial. Many studies suggest that lobe-specific selective lymph node dissection (LSLND) and lymph node sampling (LNS) can be applied to early-stage NSCLC [5][6][7][8][9][10][11]. These studies indicate that for early-stage NSCLC, LSLND and LNS can reduce operative time and some perioperative complications and have no difference in survival compared with SLND [6][7][8][9]12].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective clinical trial including 1,023 early-stage NSCLC patients showed no difference in RFS and OS between SLND and LNS (13,21). For early-stage NSCLC, several studies found no difference in survival and recurrence rate between LSLND and SLND (16,22,23).…”
Section: Discussionmentioning
confidence: 99%